THE GODUNOV METHOD FOR STEFAN PROBLEMS WITH ITS APPLICATION TO CRYOSURGERY - TARWIDI (NIM:20910002); Pembimbing : Dr. Sri Redjeki Pudjaprasetya, DEDE
In this thesis, the solutions of the Stefan problem, both one dimension and two dimensions are studied. The enthalpy formulation which is discretized by Godunov method is used to obtain the numerical solution. By using the enthalpy formulation, the governing equation of the system is the same, regardless of liquid or solid phase. In one-dimensional Stefan problem two cases are discussed. The first case, the effects of density change during phase change are ignored. This case is solved by the standard enthalpy method. The second case, the effects of density change such as volume expansion and movement of the material are taken into account. The modified enthalpy method is used to solve this case. Numerical results for both cases show good agreement with the exact solutions. The similar method is applied to two-dimensional Stefan problem. Two-dimensional simulation results for cryosurgery are demonstrated. Cryosurgery is the use of extremely cold temperatures to destroy cancer cells. In these results, the temperature profile and the interface position are shown as important information to control the cryosurgery process.